Dynamics Of Foreign Direct Investment In India After New Economic Policy: An Empirical Analysis (Journal of Namibian Studies : History Politics Culture, 2023)
It has been seen generally that Foreign Direct Investment (FDI) is helping the growth of national income growth in India. India and its neighboring countries have seen an influx of FDI with varying degrees of impact on the local economy. The relationship between FDI and economic growth has been extensively studied, with the view to establishing causality between the two. However, there have been varying results depending on the country's particular context and situation, and the results are inconclusive. This paper attempts to analyze the relationship between FDI and GDP using a time series analysis from 1990 to 2021.